2017
DOI: 10.1002/csr.1394
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Successful Implementation of Product Stewardship Strategy? The Role of Absorptive Capability

Abstract: Implementation of Product Stewardship Strategy (PSS) requires integration of ‘voices of stakeholders’ in business decisions to create ‘differentiation’ in the market place. Considering that absorptive capability (AC) is a critical aspect of organizational learning, it may deliver dynamic integration of stakeholder's expectations and know‐how in decision making. This paper attempts to link the attributes of AC with the features of PSS and presents outcomes of an empirical study of sixty Indian firms from severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 84 publications
(124 reference statements)
0
16
0
3
Order By: Relevance
“…While it does involve some of the same pollution prevention activities, other key activities involved include stakeholder engagement and supply chain integration (Bhupendra and Sangle, 2017). It also involves developing and exerting influence over the entire supply chain, thereby allowing the business to pre-empt its competitors.…”
Section: The Natural-resource Based View (Nrbv)mentioning
confidence: 99%
See 1 more Smart Citation
“…While it does involve some of the same pollution prevention activities, other key activities involved include stakeholder engagement and supply chain integration (Bhupendra and Sangle, 2017). It also involves developing and exerting influence over the entire supply chain, thereby allowing the business to pre-empt its competitors.…”
Section: The Natural-resource Based View (Nrbv)mentioning
confidence: 99%
“…Research to date has demonstrated that these strategies do lead to improvements in overall ecological impact (see Graham et al (2016) and Bhupendra and Sangle (2017) for example).…”
Section: Introductionmentioning
confidence: 99%
“…Control organizations will embrace more straightforward practices, and proactive companies will select more complex activities that indicate a higher degree of environmental stewardship. With higher degrees of environmental stewardship, organizations achieve more significant business benefits than those seeking only minimal compliance with government regulations (Bhupendra & Sangle, 2017; Guimaraes & Liska, 1995; Jabbour et al, 2012).…”
Section: Discussion: What Can Be Done?mentioning
confidence: 99%
“…They recognized that the DC perspective is suitable for studying the complex and ambiguous issue of environmental sustainability. Some other papers relating to the environmental sustainability challenge have focused attention on a particular DC, such as absorptive capacity (Bhupendra & Sangle, ), communication skills (to convince stakeholders), sustainable supplier development capability (Foerstl, Reuter, Hartmann, & Blome, ), a proactive environmental strategy (Aragon‐Correa & Sharma, ), corporate environmental innovation, corporate environmental adaptability (Wong, ), or environmental search routines (Hilliard & Jacobson, ). Overall, research on environmental sustainability DCs, although still new, is achieving some degree of recognition.…”
Section: Introductionmentioning
confidence: 99%